Pengaruh Citra Merek, Kualitas Produk dan Word Of Mouth Terhadap Keputusan Pembelian Pada Toko Sely Fashion Legian (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2025)
Currently, the fashion industry has experienced significant growth globally, including in Indonesia. Most men and women are highly concerned about their appearance. Fashion essentially serves to provide cover, protection, modesty, and appeal. However, this does not limit fashion's role in functioning as a form of self-identity for both individuals and groups. The main issue in this study is the fluctuating number of buyers at Sely Fashion Store, which shows a declining trend. Throughout 2023, the number of buyers saw a significant increase in June (48.52%), but this was followed by a continuous decline until December, reaching the lowest point of 107 buyers.The population in this study consists of 2,051 consumers. The sample size was determined using the Slovin formula with a specified margin of error, resulting in 96 consumers as respondents. The analytical method used is multiple linear regression. Data were collected through questionnaires. To ensure data quality, instrument tests were conducted, including validity and reliability tests. Data analysis was performed using SPSS software to obtain accurate results.  The findings of this study indicate that brand image, product quality, and word of mouth (WOM) partially have a positive and significant effect on purchasing decisions. Simultaneously, brand image, product quality, and WOM have a significant effect on consumer purchasing decisions at Sely Fashion Store in Legian. Based on these findings, the researcher suggests that Sely Fashion Store in Legian strengthen its brand identity through creative promotions, exclusive designs, collaborations with local designers, and special events. Consistent social media management, trend designs using premium materials, and professional visual promotions can enhance an elegant impression. Improving product quality, services, as well as referral and discount programs will strengthen customer loyalty and expand the consumer base through personal recommendations.